Beyond Cultural Relativism An Ecological Model for Rhetorical Ethics - Mackin, Jim. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
A model intended to overcome the cultural relativism of determining what is an ethical act draws an analogy to environmental studies. Beginning with the concepts of "telos" (final purpose) and "archai" (priority), the notion of an ecosystem of ethics avoids limitation to a particular historical definition of good. Since the telos of human life is the quest for the good, a communicative ecosystem's virtues are those which enable its members to seek the good. An ideal communicative system supports all parts equally, and the parts in turn support the system. The telos of the individual and of the system are interrelated; both must be taken into account in making ethical decisions. The practice of living ethically will include system building and transforming. How to help the present system become more like the ideal without making the system less viable is the central question. Combining the notions of public and private into a systems relationship should increase understanding of the problem of morality, but also will raise new inquiries. (Twenty-five notes are included.) (SG)
ERIC Note: Paper presented at the Annual Meeting of the Speech Communication Association (75th, San Francisco, CA, November 18-21, 1989).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Research; Cultural Context; Ecology; Ethics; Models; Moral Values; Research Needs; Rhetoric; Cultural Relativism; Aristotle -- Communication Theory; Speeches/Meeting Papers; Opinion Papers; Reports, Evaluative